The Effects of Inspiratory Muscle Training in Individuals With Cervical Spinal Cord Injuries: A Systematic Review and Meta-Analysis - Dat Huu Tran; Ha Thi Le; Tho Thi Quynh Chu; Hung Thi Cam Pham; Anh Ngoc Van Le (Annals of Rehabilitation Medicine)
The effect of inspiratory muscle training (IMT) on cervical spinal cord injury (SCI) remains controversial. This study aimed to assess the efficacy of IMT in enhancing breathing muscle strength, pulmonary function, and quality of life (QoL) among patients with cervical SCI. A search was performed using the PubMed, Cochrane Library, Scopus, Embase, and Web of Science databases through December 2023. This review was conducted according to PRISMA guidelines and the Cochrane Library Handbook. The meta-analysis used mean differences (MDs) or standardized mean differences to pool the results. The Risk of Bias 2 and the GRADE (Grading of Recommendations, Assessment, Development, and Evaluation) were used to assess the methodological quality of the included studies. This systematic review included five randomized controlled trials (202 participants). The results of the meta-analysis showed that IMT significantly improved maximal inspiratory pressure (MIP) with MD 12.13 cmH2O (95% confidence interval [CI] 4.22 to 20.03), maximal expiratory pressure (MEP) with MD 8.98 cmH2O (95% CI 6.96 to 11.00), and vital capacity (VC) with MD 0.25 L (95% CI 0.21 to 0.28). There were no significant improvements in forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), and QoL. The quality of the evidence ranged from very low to moderate, owing to bias and heterogeneity. Our results showed that IMT may improve MIP, MEP, and VC, but not FEV1, FVC, or QoL, in patients with cervical SCI. Further large-scale studies are required to determine this effect’s optimal dosage and duration.